Rece do góry - Skolimowski, Jerzy (Poland, 1981)
Andrzej Leszcyzc is one of several doctors attending a medical school reunion in a sealed-up railway carriage. Between drinks, the disenchanted medicos ruminate over the effect that communism (particularly the Stalinist brand) has had on their profession.
Keywords: Fiction films